-HEPATOPROTECTIVE AND HYPOLIPIDEMIC EFFECTS OF BIS [4-(4'-HYDROXY-3'-METHOXYBEZYLIDINEAMINOPHENYL) ]TELLURIDE (R2TE) AGAINST SODIUM NITRITE INTOXICATION IN MALE ALBINO RATS. - Mohammed A. Al-Diwan Shaker A. S. N. AL; Hiathem J. Kadhum; Jadaan (Basrah Journal of Veterinary Research)
Sodium nitrite is widely used as a color fixative and preservative in meat and fish. Impairment of hepatic function and disturbances in lipid metabolism are well recognized adverse effects of sodium nitrite. The aim of this study is to investigate the role of bis [4-(4'-hydroxy-3'-methoxybezylidineaminophenyl)]telluride, a novel compound, in preventing the hepatic damage and disturbances of lipid metabolism induced by sodium nitrite toxicity in male albino rats. The estimated LD50 of [4-(4'-hydroxy-3'-methoxybezylidineaminophenyl)]telluride in adult male albino rats is 218.7 mg/kg body weight. Rats given sodium nitrite (0.2%) in the drinking water showed a significant increase in serum ALT, AST, ALP, Total cholesterol, TG. LDL and VLDL while HDL significantly reduced. These changes are reversed by administration of bis [4-(4'-hydroxy-3'-methoxybezylidineaminophenyl)]telluride in a dose of 11mg/kg body weight corresponding to 1/20 LD50. It is concluded that bis [4-(4'-hydroxy-3'-methoxybezylidineaminophenyl)]telluride is effective in preventing hepatic damage and dislipidemia in sodium nitrite intoxicated male rats.